2008
DOI: 10.4049/jimmunol.180.6.3627
|View full text |Cite
|
Sign up to set email alerts
|

NKT Cells in Tumor Immunity: Opposing Subsets Define a New Immunoregulatory Axis

Abstract: NKT cells are true Ag-specific T cells that also have innate properties and form a bridge between the innate and adaptive immune systems. Distinct NKT cell subsets play positive and negative regulatory roles and define a new immunoregulatory axis with broad implications for tumor immunity and other immunological and disease settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(90 citation statements)
references
References 126 publications
(124 reference statements)
2
88
0
Order By: Relevance
“…Two other groups already ruled out the involvement of FBS response by measuring tumor growth in mice injected with DC exposed to mouse serum [12,15], and we likewise confirmed IFN-g secretion by NK cells in mice immunized with DC cultured in mouse serum. In immunosurveillance, some types of CD4 + cells including CD4 + CD25 + Treg cells [27,28] and type II NKT cells have suppressive effects on tumor immunity [29]. Ambrosino et al [30] were able to suppress immune surveillance with selective stimulation of CD4 + type II NKT cells, which are CD1d-dependent, but not iNKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two other groups already ruled out the involvement of FBS response by measuring tumor growth in mice injected with DC exposed to mouse serum [12,15], and we likewise confirmed IFN-g secretion by NK cells in mice immunized with DC cultured in mouse serum. In immunosurveillance, some types of CD4 + cells including CD4 + CD25 + Treg cells [27,28] and type II NKT cells have suppressive effects on tumor immunity [29]. Ambrosino et al [30] were able to suppress immune surveillance with selective stimulation of CD4 + type II NKT cells, which are CD1d-dependent, but not iNKT cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fewer liver NKT cells were detected in IL-1␣ Ϫ/Ϫ mice than in WT mice. CD1d-restricted invariant NKT cells play a pivotal role in natural antitumor immune responses, mainly by activation of innate and adaptive immunosurveillance cells swift and potent cytokine secretion (45). Finally, in comparison to effector cells from WT mice, innate and specific antitumor effector cells from IL-1␣ Ϫ/Ϫ mice, i.e., NK cells, LAK cells, and CTL, displayed a reduced killing capacity, which correlated with reduced expression of perforin and granzyme B in purified NK cells from IL-1␣ Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…CD1d prevents the activation of both iNKT and variant NKT cells that exert opposing functions, 57,58 and this may complicate the interpretation of the results obtained by Rhee et al In a subsequent study, Ragin et al 59 found a trend for protection from lethal toxic shock in Balb/ c.CD1d À/À and Balb/c.Ja18 À/À mice receiving D-galactosamine and SEB in comparison with wild-type Balb/c mice challenged with the same agents. Although reporting both interesting and important results, these studies did not address the direct effect of SAgs on iNKT cells or on human iNKT cell responses.…”
Section: Human Inkt Cells Are Activated By Bacterial Sagsmentioning
confidence: 99%